2002
DOI: 10.1086/338928
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Pneumococcal Carriage in Mice by Subcutaneous Immunization with Peptides from the Common Surface Protein Pneumococcal Surface Adhesin A

Abstract: Pneumococcal surface adhesin A (PsaA), a common protein expressed on all 90 pneumococcal serotypes, is a vaccine candidate. Three anti-PsaA monoclonal antibody phage display-expressed monopeptides (15 mers), in various formulations as lipidated or nonlipidated multiantigenic peptides or as bi- or tripeptide constructs, were studied in a mouse nasopharyngeal carriage model to determine the inhibitory effect of induced antibodies on carriage of pneumococcal serotypes 2, 4, and 6B. Antibodies to each of the vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
20
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 46 publications
1
20
0
Order By: Relevance
“…Three out of four prominent bands recognized by cross-reactive antibody on May 9, 2018 by guest http://iai.asm.org/ were found to be surface-associated proteins. Each of these three proteins, PspA, PpmA, and PsaA, has been previously proposed as a vaccine candidate or shown to induce protective responses when given as a purified protein together with an adjuvant (6,12,37), although evidence for cross-protection against colonization elicited by these purified antigens is more limited (6,22). Our results provide an unbiased confirmation of the potential of each of these antigens to induce a crossreactive immune response.…”
Section: Discussionsupporting
confidence: 68%
“…Three out of four prominent bands recognized by cross-reactive antibody on May 9, 2018 by guest http://iai.asm.org/ were found to be surface-associated proteins. Each of these three proteins, PspA, PpmA, and PsaA, has been previously proposed as a vaccine candidate or shown to induce protective responses when given as a purified protein together with an adjuvant (6,12,37), although evidence for cross-protection against colonization elicited by these purified antigens is more limited (6,22). Our results provide an unbiased confirmation of the potential of each of these antigens to induce a crossreactive immune response.…”
Section: Discussionsupporting
confidence: 68%
“…It is important to note that, although we have demonstrated that PsaA and PpmA are poor vaccine targets for protection against systemic pneumococcal infection (at least under the present experimental conditions) on the basis of their inaccessibility to antibodies, other studies have demonstrated that mucosal immunization of mice with PsaA is highly protective against pneumococcal carriage (5,7,11,23). The exact mechanisms of protection against pneumococcal carriage afforded by immunization with PsaA have not yet been elucidated.…”
Section: Discussionmentioning
confidence: 68%
“…Previous studies from several laboratories have shown that PsaA immunization is most effective against nasopharyngeal colonization (18,35,37). However, the effectiveness of PsaA immunization against systemic pneumococcal challenges varies in different studies (14,43).…”
Section: Discussionmentioning
confidence: 99%